P1186PRELIMINARY RESULTS OF THE FIRST PHASE II CLINICAL TRIAL ON THE USE OF AN INNOVATIVE GLUCOSE-SPARING PD SOLUTION (FIRST). (6th June 2020) - Bonomini, Mario; Lombardi, Teresa; Di Fulvio, Giorgia; Gigante, Anna; Di Liberato, Lorenzo; Russo, Roberto; Gesualdo, Loreto; Rago, Carmela; Iacobelli, Massimo; Arduini, Arduino
Abstract: Background and Aims: High amounts of glucose as the main osmotic agent for peritoneal dialysis (PD) could be harmful, as it may significantly increase cardiovascular morbidity and mortality. Glucose has long-term detrimental effects on the peritoneum, which ultimately may result in ultrafiltration failure, worsening fluid overload and cardiovascular disease. The absorption of glucose from the dialysate accentuates the disturbances of the carbohydrate metabolism, which is already impaired in the uremic state, leading to insulin resistance. XyloCore (Iperboreal Pharma, Pescara, Italy), is a low glucose containing PD solution (PDS) proposed as an alternative to glucose PDS only regimen. It has been formulated replacing most of the glucose with two crystalloid agents, D-xylitol and L-carnitine. PDS containing osmolar agents like xylitol and L-Carnitine added to glucose, used for the nocturnal exchange, may lead to a significant reduction of glucose level in PDS during the night dwell, while preserving or even improving the depurative efficacy of the standard PDS containing 2.5% glucose. The reduction of glucose level could be further enhanced if the PDS with xylitol and carnitine will be used for the diurnal exchanges and a PDS with icodextrin will substitute the standard PDS containing glucose 2.5% for the nocturnal dwell. The aims of the study are to evaluate the effects of (I) the XyloCore PDS IPX15 [containing glucose (0.5%), xylitol (1.5%) and L-carnitine (0.02%) as osmotic agents, as compared to the standard 2.5% glucose PDS] for the nocturnal exchange, and (II) the XyloCore PDS IPX07 [containing glucose (0.5%), xylitol (0.7%) and L-carnitine (0.02%), as compared to the standard 1.5% glucose PDS] for the diurnal (short dwell) exchanges. Method: Prospective, randomized, controlled clinical trial in stable ESRD patients treated by CAPD (study protocol registered as NCT 04001036). Key inclusion criteria are: ESRD treated for at least three months with CAPD, stable clinical condition within the four weeks before the screening, hemoglobin ≥ 9g/dL, absence of acute peritonitis and/or peritoneal catheter infection in the three months before. Key exclusion criteria are: androgen therapy, active infections, congestive heart failure stage III and IV NYHA; major cardiovascular events in the last 3 months, clinically relevant cardiac arrhythmia; clinically relevant abnormal hepatic tests; treatment with L-carnitine in the previous three months, pregnancy, life expectancy of less than one year, allergy to L-carnitine or xylitol. The sample size is 40 patients. Treatment duration is 4 weeks plus a 4 weeks safety follow up with no treatment. Primary end-point is the daily peritoneal ultrafiltration volume. Secondary end-points are the peritoneal equilibration test (D/P creatinine, D/P glucose), weekly total Kt/V urea, weekly total creatinine clearance, Adverse Events. Results: Two centers participate in the study. One center has so far recruited 10 patients, 6 in the IPX15 group and 4 in the IXP07 group. The six patients in the IXP15 group were 4 males and 2 males, aged 69.5 ±5.1 years. The four patients in the IXP07 were all male, mean age 56 ± 12 years. One patient already completed the study period. Results for Kt/V, creatinine clearance, D/P creatinine, D/P glucose, ultrafiltration volume, at time (T) 0 are 1.17, 85.6, 0.75, 0.18, 400 ml, respectively; at T28 (days) are 3.1, 80, 0.82, 0.23, 400 ml respectively, and at T56 are 3.5, 80, 0.77, 023, 450 ml, respectively. D/P glucose results indicate that this patient is a high transporter and D/P creatinine that the patient was an average/ high transporter. There were no adverse events reported and tolerability has been excellent so far. Conclusion: In the first 10 ESRD patients included in the study, XyloCore PDS used for 4 weeks has been well tolerated without significant adverse events. The study is in progress.